Kaizala-Based Teaching Materials Oriented to Students' Numerical Ability and Interest in Learning - Dea Siti Fikriyah; Supianti, In In; YANIAWATI, POPPY; Ana Setiani; Rani Sugiarni (UNNES JOURNAL, 2025)
The current low level of students' numeracy ability has not been matched by the in-depth use of digital platforms such as Microsoft Kaizala. Therefore, this research aims to develop Mobile Learning-based teaching materials assisted by Microsoft Kaizala, focusing on students' numeracy ability and learning interest. The developed teaching materials were analyzed for their feasibility and effectiveness in improving students' numeracy ability and learning interest by two media experts and four material experts. The research utilized the Research and Development model ADDIE, involving 34 junior high school students in the city of Bandung. Instruments used included validation sheets, questionnaires, interviews, and numeracy skill tests. Data were analyzed using effect size, Pearson correlation, and descriptive statistics. The results of the research indicate: (1) The teaching materials are considered feasible by content experts and highly suitable by media experts; student responses fall into the excellent category. (2) Students' numeracy ability are categorized as moderate. (3) Students' learning interest is categorized as good. (4) The teaching materials are effective in improving students' numeracy ability. (5) There is no correlation between students' numeracy ability and learning interest. Therefore, the teaching materials can be utilized in mathematics learning based on m-learning. Integrating digital platforms into teaching materials can be a practical solution for teachers to optimize flexible and interactive numeracy learning. Abstrak Rendahnya kemampuan numerasi siswa saat ini belum diimbangi dengan pemanfaatan platform digital seperti Microsoft Kaizala secara mendalam. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan bahan ajar berbasis Mobile Learning berbantuan Microsoft Kaizala yang berorientasi pada kemampuan numerasi dan minat belajar siswa. Bahan ajar yang dikembangkan dianalisis kelayakan dan efektivitasnya pada kemampuan numerasi dan minat belajar siswa oleh dua orang ahli media dan empat orang ahli materi. Penelitian ini menggunakan metode Research and Development model ADDIE yang melibatkan 34 siswa SMP di Kota Bandung. Instrumen yang digunakan adalah lembar validasi, angket, wawancara, dan tes kemampuan numerasi. Data dianalisis menggunakan effect size, Pearson correlation, dan deskriptif. Hasil penelitian menunjukkan: (1) Bahan ajar termasuk kategori layak dari ahli materi dan sangat layak dari ahli media, berdasarkan respon siswa berada pada kategori sangat baik; (2) Kemampuan numerasi siswa termasuk dalam kategori sedang; (3) Minat belajar siswa termasuk dalam kategori baik; (4) Bahan ajar efektif untuk meningkatkan kemampuan numerasi siswa; dan (5) Tidak terdapat korelasi antara kemampuan numerasi dan minat belajar siswa. Sehingga bahan ajar dapat digunakan dalam pembelajaran matematika berbasis m-learning. Integrasi platform digital dalam bahan ajar dapat menjadi solusi praktis bagi guru untuk mengoptimalkan pembelajaran numerasi yang fleksibel dan interaktif.